The survival of dugnad. Exploring the meanings and adaptabilities of dugnad as a concept and function in contemporary Norwegian society - Ługowska, Ewa Małgorzata (UiT Norges arktiske universitet, 2021)
The thesis explores the concept of dugnad, its meanings, and functions in contemporary Norwegian society. Dugnad is a tradition of unpaid voluntary work that can be traced back to agricultural society. Despite Norway undergoing substantial social, political and economic changes, it did not lose its relevance. In my thesis, I attempt to answer why practice so old prevailed in the modern world and how it evolved throughout centuries. By employing methods of participant observation and in-depth interviews with people participating in dugnads, I show the plethora of ways in which dugnad as a term is used, cultural norms on which it is based, and personal motivations for active involvement. Visiting dugnads in different places and contexts is a ground for comparisons and juxtaposition between urban and rural dugnads. Fieldwork has been conducted in northern Norway. Additionally, I discuss the topic of northern Norwegian identity and its complex relationship to the South.